A Theoretical Comparative Analysis Of Dna Techniques Used In Dna Based Cryptography - Nik Azura Nik Abdullah; Nur Hafiza Zakaria; Farida Hazwani Mohd Ridzuan; Azuan Ahmad; Kamaruzzaman Seman; Suriyani Ariffin; Azni Hazlizan Ab Halim (Penerbit UMT, 2024)
Indexed by SCOPUS/ERA/MYCITE